Who will defend democracy? Evaluating tradeoffs in candidate support among partisan donors and voters. Issue 1 (2nd January 2022) - Carey, John; Clayton, Katherine; Helmke, Gretchen; Nyhan, Brendan; Sanders, Mitchell; Stokes, Susan
ABSTRACT: Scholars and pundits fear that the American public's commitment to democracy is declining and that citizens are willing to embrace candidates who would trample democratic principles. We examine whether violations of those principles generate resistance from voters and/or top campaign donors and whether such resistance extends across partisan lines. In a conjoint survey experiment, we investigate how regular Americans and donor elites trade off partisanship, policy positions, and support for democratic values when choosing between hypothetical political candidates. Our findings indicate that both citizens and donors punish candidates who endorse violations of democratic principles irrespective of the candidate's party. However, partisans react very differently to candidates who support voter identification laws that threaten access to the franchise. This polarized response is especially strong among donors. These results suggest that the public and donors may sometimes be willing to forgive transgressions against democratic norms that align with their partisan and policy preferences.